Local Autonomy and Inter-Sector Performance-Based-Governance in Lampung Province - DARMASTUTI, ARI (Jurnal Studi Pemerintahan, 2014)
The dramatic shift in the management of local governmentin Indonesia, from the centralised, authoritarianNew Order Era to the more democratic ReformationEra since 1996, met public demands for,among other things, more accountability.Decentralised local government requires a systemthat allows the Central Government to supervise and,at the same time, gives local governments the capacityto carry out their duties. This paper comparesthe institutional capacity of three regencies inLampung using a ten-part inter-sector performanceevaluation method developed by the SustainableCapacity Building for Decentralization , projectfunded by the Indonesian Ministry of Home Affairs.Three separate surveys between 2007-2011 used thedata from a 10% sample of all civil servants ineach rank. We show that local government institutionalcapacities in Lampung Province differ not onlyregionally, but also within inter-sectors functions. Allthree regencies performed poorly in the inter-sectorfunction of information and communication, andall three performed best in procurement of goodsand services. In terms of local autonomy, the singlerecipe of symmetric decentralization which appliessimilarly all over Indonesia, needs to be replaced,we suggest, with asymmetric decentralization, whichis more suited to the local governments’ varied institutionalneeds.Keywords: local autonomy, inter-sector performancebased governance